ON IMPROVING THE EFFECTIVENESS OF SYSTEM-ON-ACHIP TEST DATA COMPRESSION BASED ON EXTENDED FREQUENCY DIRECTED RUN-LENGTH CODES - El-Maleh, Aiman H. (2020)
One of the major challenges in testing a System-on-a-Chip (SOC) is dealing with the large test data size. To reduce the volume of test data, several test data compression techniques have been proposed. Frequency-directed run-length (FDR) code is a variable-to-variable run length code based on encoding runs of 0’s. In this work, we demonstrate that higher test data compression can be achieved based on encoding both runs of 0’s and 1’s. We propose an extension to the FDR code and demonstrate by experimental results its effectiveness in achieving higher compression ratio.